Brothers in Arms: Features of the Ukraine – NATO Partnership in the 1990s. - Meleshchenko, Tetiana (Studia Warmińskie, 2021)
The article is devoted to the study of Ukraine-NATO relations in the 90s. of the XX century. The author made an attempt to define the main directions of Ukraine’s foreign policy after independence, to consider the multi-vector approach as a historically determined necessity in the transition period. Full integration into EuroAtlantic structures could not be fully implemented at that time, as Ukraine remained in the field of interests of Russia, which sought to restore its position in the postSoviet space and become a new center of power. Ukraine was forced to maneuver between East and West in order to establish itself in the international field and take its place in the European security architecture. The article analyzes the factors that influenced the process of establishing cooperation between Ukraine and NATO, in particular the geopolitical situation between East and West, lack of political will, and internal political problems. It can be concluded that in the 1990s, Ukraine-NATO relations developed quite rapidly, but not enough for Ukraine to become a member of NATO. However, given the unique position of the country, which received a direct border with NATO member countries, Ukraine was able to obtain the status of a special partner, which further contributed to the deepening of bilateral relations.